Pengaruh Promosi Media Sosial,Word Of Mouth Dan Kualitas Layanan Terhadap Minat Beli Konsumen (Studi Kasus Pada Toko Raja Hp Tenggarong - Muhammad Saifulloh; Sugeng Raharjo (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract: The purpose of this study was to determine the effect of promotion through social media, word of mouth and service quality on buying interest at Raja HP ​​Tenggarong simultaneously and partially. The number of respondents is 100 respondents. The results of this study indicate that simultaneously all independent variables (Promotion through social media, Word of Mouth and Service Quality) in this study have a significant effect on the dependent variable (Purchase Interest) with a significance value of 0.000 <0.05 and F count > F table ( 50,528 > 2.70). Partially, Social Media Promotion Variables have no significant effect on buying interest. Word of Mouth and Service Quality variables have a significant positive effect on Purchase Intention. Based on the results of data analysis, the dominant variable influencing buying interest is service quality. Adjusted R Square of 0.600 equals 60%. This value indicates that 60% of buying interest is influenced by promotions through social media, Word Of Mouth, and Service Quality, while the remaining 40% is influenced by other factors. Keywords: Promotion, Social Media, Word Of Mouth, Quality of Service, and Purchase Interest